(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The collected premiums and the compensations paid are among the main variables that have a prominent role in determining the level of financial solvency of insurance companies, as the higher the financial solvency of the insurance company, the more attractive it is to the target audience to acquire the company’s insurance services. Hence the importance of the issue of the solvency of insurance companies, as it is one of the critical matters on which the effectiveness of the insurance company and its continuation in the labor market depend. In this research, we try to clarify the role of collected premiums and compensations paid in determining the level of operational solvency of the Iraqi General Insurance Company. In this research, we try to clarify the role of collected premiums and compensations paid in determining the level of operational solvency of the Iraqi General Insurance Company for the period (2006-2017) by analyzing data on premiums and compensation, and the research reached a number of conclusions, the most important of which is that the study variables have a prominent role and Essential to the company’s financial solvency and ability to survive. Finally, the researcher reached a set of recommendations, the most prominent of which is a review of the risk analysis policy and a more stringent policy in accepting the risks, which will be reflected positively by reducing compensation and increasing the financial solvency of the company.